1997
DOI: 10.1021/la9708039
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of CH4−CF4 Mixtures in Silicalite:  Simulation, Experiment, and Theory

Abstract: Grand canonical Monte Carlo (GCMC) simulations of binary Lennard-Jones mixtures in the zeolite silicalite have been used to predict the adsorption of CH4 and CF4 mixtures as a function of gas phase composition, total pressure, and temperature. For single components and mixtures, predictions of adsorption isotherms and isosteric heats are in good agreement with experiment at room temperature. Within the experimental pressure range of 0 to 17 bar, the mixtures are well described by the ideal adsorbed solution (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
141
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 38 publications
7
141
0
Order By: Relevance
“…Grand canonical Monte Carlo (GCMC) simulation is a powerful tool to understand molecular behavior and structure in nanopores. It has been used to evaluate and estimate the unique behaviors of simple molecules such as N 2 , Ar, and 2 ISRN Nanotechnology CH 4 adsorbed in nanopores [16][17][18][19][20][21][22][23][24]. However, molecular simulation of a cyclic hydrocarbon is much more difficult because of its complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Grand canonical Monte Carlo (GCMC) simulation is a powerful tool to understand molecular behavior and structure in nanopores. It has been used to evaluate and estimate the unique behaviors of simple molecules such as N 2 , Ar, and 2 ISRN Nanotechnology CH 4 adsorbed in nanopores [16][17][18][19][20][21][22][23][24]. However, molecular simulation of a cyclic hydrocarbon is much more difficult because of its complexity.…”
Section: Introductionmentioning
confidence: 99%
“…They have investigated the idea of analyzing the influence of several factors such as temperature, pressure, chemical composition, zeolite topology, and pore size on the adsorption [204,[208][209][210][211][212][213][214] and transport [124,203,205,[215][216][217][218] of these mixtures. For example, Krishna et al reported molecular simulations for the self-diffusion of pure and equimolar mixture of carbon dioxide and methane in DDR, CHA, and MFI structures [205], and in a follow-up study, by using MC and MD simulations, screened 12 zeolite topologies looking for the optimal structure to separate the mixture, thereby finding the highest permeation selectivities for DDR and CHA zeolites [214].…”
Section: Summary and Outlook 353mentioning
confidence: 99%
“…Binary truncated and shifted LJ fluids in a slit-shaped pore made of LJ silica were employed as a model sys- Interactions with silicon atoms were neglected and only the bound oxygen atoms were considered as the interaction sites, as assumed in many of the previous related studies (Heuchel et al 1997). For oxygen, the parameters ε/k and σ were determined as 230.0 K and 0.27 nm, respectively (Brodka and Zerda 1996).…”
Section: Simulation In Which Bulk Liquid Is Realistically In Contamentioning
confidence: 99%